Persepsi dan Harapan Konsumen terhadap Produk Beras dalam kemasan di UD. Sahabat Tani Kabupaten Sidoarjo - Kusuma, Randy Cahaya; Hidayat, Syarif Imam; Mubarokah, Mubarokah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Food security in Indonesia is highly dependent on the availability of quality rice, which is consumed by around 98% of the population. In this context, rice packaging plays an important role in attracting consumers' attention and ensuring product safety. This study aims to analyze consumer perceptions and expectations of packaged rice products sold by UD. Sahabat Tani in Sidoarjo Regency. The research method used is quantitative research with a descriptive approach. Primary data was collected through observations, interviews, and questionnaires distributed to 30 consumers who had purchased rice products from UD. Sahabat Tani. The results of the study showed that consumer perception of rice variables received an average score of 2.89 with a high category, especially in the indicators of color, taste, grain shape, aroma, and cleanliness. For packaging variables, consumer perception received an average score of 2.88, with attractive packaging indicators, impressions of packaging, product safety, information on packaging, and packaging comfort. The distribution variable also received a high rating with an average score of 3.13, which includes the affordability and availability of the product. The GAP analysis shows that there is a gap between consumer perception and expectations, with consumer expectations having higher values on all variables. Improved rice quality, packaging design, and better distribution strategies are needed to meet consumer expectations and increase their satisfaction and loyalty.